The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1515/macvetrev-2017-0031
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic Resistance and Associated Management Practices in Local Horses in Sokoto Metropolis, Nigeria

Abstract: This study was carried out to assess the management practices used in the control of gastrointestinal (GI) nematodes of horses and to determine the efficacy of three anthelmintics commonly used in Sokoto metropolis. A questionnaire was administered on management practices, while an anthelmintic efficacy test was carried out using 15 horses. The 15 horses were divided into three groups (A, B and C) comprising of 5 each and treated with albendazole, ivermectin and fenbendazole, respectively. The faecal egg count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…One theoretic consequence derived from frequent whole-herd deworming is the reduction of parasite population in refugia, and a resulting faster development of anthelmintic resistance (Peregrine et al 2014;Leathwick et al 2019). Nevertheless, cyathostomin populations in tropical areas have been documented to have developed resistance even when exposed to a comparatively low treatment intensity (Kumar et al 2016;Seyoum et al 2017;Mayaki et al 2018;Salas-Romero et al 2018). Computer modeling studies have demonstrated that anthelmintic resistance develops faster in tropical and subtropical areas compared to temperate areas, even after the application of SAT (Nielsen et al 2019;Sauermann et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…One theoretic consequence derived from frequent whole-herd deworming is the reduction of parasite population in refugia, and a resulting faster development of anthelmintic resistance (Peregrine et al 2014;Leathwick et al 2019). Nevertheless, cyathostomin populations in tropical areas have been documented to have developed resistance even when exposed to a comparatively low treatment intensity (Kumar et al 2016;Seyoum et al 2017;Mayaki et al 2018;Salas-Romero et al 2018). Computer modeling studies have demonstrated that anthelmintic resistance develops faster in tropical and subtropical areas compared to temperate areas, even after the application of SAT (Nielsen et al 2019;Sauermann et al 2019).…”
Section: Discussionmentioning
confidence: 99%